2017
DOI: 10.1001/jama.2017.4011
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Thyroid Cancer

Abstract: he US Preventive Services Task Force (USPSTF) makes recommendations about the effectiveness of specific preventive care services for patients without obvious related signs or symptoms.It bases its recommendations on the evidence of both the benefits and harms of the service and an assessment of the balance. The USPSTF does not consider the costs of providing a service in this assessment.The USPSTF recognizes that clinical decisions involve more considerations than evidence alone. Clinicians should understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(44 citation statements)
references
References 27 publications
1
35
0
8
Order By: Relevance
“…Consistent with previous studies (10, 11), we report an increased incidence of CHD and ischemic stroke among thyroid cancer patients compared to controls and showed that post-thyroidectomy levothyroxine dosage, which serves as a proxy marker for level of TSH suppression, is a key factor in such risk. Our study suggests that cardiovascular risk should be taken into consideration when the target level for TSH suppression is determined (6), and support recent recommendations that called for a more cautious approach in the screening and treatment of thyroid cancer and subsequent TSH suppression therapy (19,20). The pathophysiological mechanism for increased incidence of CHD and ischemic stroke remains largely unknown (10).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Consistent with previous studies (10, 11), we report an increased incidence of CHD and ischemic stroke among thyroid cancer patients compared to controls and showed that post-thyroidectomy levothyroxine dosage, which serves as a proxy marker for level of TSH suppression, is a key factor in such risk. Our study suggests that cardiovascular risk should be taken into consideration when the target level for TSH suppression is determined (6), and support recent recommendations that called for a more cautious approach in the screening and treatment of thyroid cancer and subsequent TSH suppression therapy (19,20). The pathophysiological mechanism for increased incidence of CHD and ischemic stroke remains largely unknown (10).…”
Section: Discussionsupporting
confidence: 82%
“…If the long-term risk of cardiovascular events revealed in our study is additionally taken into consideration, the benefits of screening and aggressive therapy would be mitigated to some degree. The US Preventive Services Task Force (USPSTF) recently recommended against screening for thyroid cancer in asymptomatic adults (20).…”
Section: Discussionmentioning
confidence: 99%
“…Examination of the mechanisms that drive overdiagnosis and overtreatment of thyroid cancer is urgently warranted. Due notably to the harms of overdiagnosis, the US Preventive Services Task Force has recently updated its recommendation against routine screening for thyroid cancer (D level recommendation) [38, 41]. To identify which patients could benefit from the detection of early stage cases, a risk-based screening with combined diagnostic and prognostic tools (biomarker, personalized medicine) could be a promising approach to tailor prevention and screening according to the individual risk of thyroid cancer [42].…”
Section: Discussionmentioning
confidence: 99%
“…In order to limit this phenomenon, the US Preventive Services Task Force recommends against thyroid screening in the general population (4). This statement does not apply to subjects with recognized risk factors of thyroid cancer (i.e.…”
Section: Introductionmentioning
confidence: 99%